Highly dispersed of Ag/AgCl nanoparticles on exfoliated FeOCl nanosheets as photo-Fenton catalysts for pollutants degradation via accelerating Fe(II)/Fe(III) cycle. (June 2022) - Wang, Lina; Yang, Hanpei; Kang, Li; Wu, Mi; Yang, Yuankun
Abstract: In this work, Ag/AgCl/FeOCl (Ag–Fe) catalysts were successfully prepared via multistep routes in which Ag was uniformly anchored to the enriched Cl sites provided by exfoliated FeOCl nanosheets. Among these Ag–Fe catalysts, 5% Ag–Fe exhibited the highest pseudo first-order kinetic constant 0.1056 min −1 for photo-Fenton degradation of Rhodamine B (RhB), which was 11 times higher than that of FeOCl (0.0096 min −1 ). Ag–Fe catalysts exposed more coordinatively unsaturated Fe active sites to coordinate with H2 O2 due to the cleavage of Fe–Cl bond. The exposed coordinatively unsaturated Fe(III) active sites could capture the photoinduced electrons and reduce them to Fe(II), which boosted the separation efficiency of photogenerated charge carriers. Meanwhile, the photogenerated electrons of Ag 0 transferred to the FeOCl, promoting the reduction of Fe(III) to Fe(II). In addition, the intensified visible light adsorption (SPR effect) was achieved after introducing Ag/AgCl nanoparticles on exfoliated FeOCl. Hydroxyl radicals (·OH) and holes (h + ) were determined as the main reactive oxidative species (ROS) in the photo-Fenton degradation process. Graphical abstract: Image 1 Highlights: Highly dispersed of Ag/AgCl on exfoliated FeOCl nanosheets (Ag–Fe) was synthesized by a multistep method. Enhanced photo-Fenton catalytic activity for RhB degradation was achieved under visible light. Ag–Fe possessed rich coordinatively unsaturated Fe active sites to coordinate with more H2 O2 . The photogenerated electrons from Ag/AgCl accelerated the cycle of Fe(II)/Fe(III).